2012
DOI: 10.1093/bioinformatics/bts589
|View full text |Cite
|
Sign up to set email alerts
|

miR-EdiTar: a database of predicted A-to-I edited miRNA target sites

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…There are other examples of RNA editing in cancer (see review by Skarda et al [125]), as well as databases compiling particular miRNA sequences subject to RNA editing[126]. Overall, it is clear that RNA editing is modified in tumors on a global scale; however, more work is required to understand the role of miRNA editing in the processes of tumorigenesis.…”
Section: Regulating the Regulators – How Many Ways?mentioning
confidence: 99%
“…There are other examples of RNA editing in cancer (see review by Skarda et al [125]), as well as databases compiling particular miRNA sequences subject to RNA editing[126]. Overall, it is clear that RNA editing is modified in tumors on a global scale; however, more work is required to understand the role of miRNA editing in the processes of tumorigenesis.…”
Section: Regulating the Regulators – How Many Ways?mentioning
confidence: 99%
“…A-to-I RNA editing has been discovered to occur in both intronic and exonic regions, 5 -and 3'-UTRs as well. RNA editing events can take place in several cellular contexts: in the gene expression pathway [Bazak et al, 2014], such as in the creation and/or destruction of splicing sites [Emeson et al, 1999] or in translation [Nishikura, 2010]; during gene regulation in miRNA/mRNA-binding regions [Nishikura, 2006;Borchert et al, 2009;Laganà et al, 2012]. Recently, it has been observed that RNA editing may occur in ncRNAs, particularly in pre-tRNAs [Su and Randau, 2011], pri-miRNAs [Kawahara et al, 2008;Kawahara, 2012], lncRNAs [Mitra et al, 2012], and lately piRNAs [Yang et al, 2015] and circRNAs [Ivanov et al, 2015].…”
Section: Detection and Evaluation Of Rna Modification Eventsmentioning
confidence: 99%
“…A-to-I editing is very widespread in the human genome [4] and spans both coding and non-coding regions, mainly within highly repetitive Alu elements, which can form the requisite double-stranded structure for ADAR-mediated editing. RNA editing has been shown to create different protein isoforms [5], modulate alternative splicing [6], and regulate transcript stability by modifying microRNAs and microRNA binding sites [7,8]. In the context of cancer, as this recent work shows, RNA editing may serve as an additional, and much more dynamic and flexible, counterpart to genomic-level mutations.…”
mentioning
confidence: 99%